MIndreader [videorecording (DVD)] - Christiano, Rich, 1956-; Briggs, Hamish; Keene, Connor; Turner, Ross (Five & Two Pictures, 2022)
The year is 1974 and The Great Dexter is the closing act in a variety show at The Temple Theatre. His amazing mindreading act fools everyone, including the local magicians' association. As Dexter's popularity grows, so does the association's jealousy as they try to shut his act down and figure out how it's done.